Harmful Algal in Banyuasin Coastal Waters, South Sumatera - Aryawati, Riris; Bengen, Dietriech Geoffrey; Prartono, Tri; Zulkifli, Hilda (Biosaintifika: Journal of Biology & Biology Education, 2016)
Phytoplankton have important as food-chain major component and primary production of marine environment. However, high abundance of phytoplankton could give harmful effects toward water ecosystem. Moreover, they could produce toxic substances that will be accumulated within their consumer. This accumulation could be dangerous for human or animals.This research were aimed to determine and calculatespecies of harmful algae in Banyuasin coastal waters. The study was conducted on April, June, August, October and December of 2013, and in February 2014, at ten stations. Phytoplankton samples were taken vertically using plankton nets. In the form of cone-shaped with a diameter of 30 cm, length 100 cm and mesh size 30 ?m.The result showed that there are 35 genera of phytoplankton. That have been found and consisted of four groups; Bacillariophyceae, Dinophyceae, Cyanophyceae and Chlorophyceae. 13 species were identified as Harmful Algal (Chaetoceros, Coscinodiscus, Nitzschia, Skeletonema, Thalassiosira, Alexandrium, Ceratium, Dinophysis, Noctiluca, Protoperidinium, Prorocentrum, Anabaena dan Oscillatoria), with seven of them were known for having toxin (Nitzschia, Alexandrium, Dinophysis, Protoperidinium Prorocentrum, Anabaena and Oscillatoria). Monitoring result showed that the highest number of species of potential harmful algal blooms (HABs) occured in June and the highest abundance occured in August, especially Chaetoceros and Skeletonema.How to CiteAryawati, R., Bengen, D. G., Prartono, T., & Zulkifli, H. (2016). Harmful Algal in Banyuasin Coastal Waters, South Sumatera. Biosaintifika: Journal of Biology & Biology Education, 8(2), 231-239.